2021
DOI: 10.1007/s12011-021-02974-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Toxic Metals (Al, Cd, Pb) and Trace Elements (B, Ba, Co, Cr, Cu, Fe, Mn, Mo, Li, Zn, Ni, Sr, V) in the Common Kestrel (Falco tinnunculus) from the Canary Islands (Spain)

Abstract: The monitoring of trace elements and toxic metals in apical predators of the trophic chain provides data on the degree of contamination in ecosystems. The common kestrel is one of the most interesting raptors in this respect in the Canary Islands; therefore, the study of the levels of trace elements and toxic metals in this species is of much scientific value. The content of trace elements and toxic metals (B, Ba, Co, Cr, Cu, Fe, Mn, Mo, Li, Zn, Ni, Sr, V, Al, Cd, Pb) was determined in the liver, muscle, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(77 reference statements)
0
2
1
Order By: Relevance
“…Similar to our results, in addition to predatory birds, the highest proportions of Zn and Cu were detected in the feathers of the other groups of birds including the water birds, omnivores, insectivore-frugivores, insectivores, and granivores. These metals might have a preference for the pigments that give birds their coloring, for example, the darker black and iridescent blue feathers contained considerable amounts of Fe and Cu, while Zn was noticed in the iridescent feathers [48,49]. The feather Cd levels of the six groups of birds in the present study were below the threshold level (2 ppm), but the Pb concentrations were critically above the threshold (4 ppm) that affects reproductive success in birds [7,43].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Similar to our results, in addition to predatory birds, the highest proportions of Zn and Cu were detected in the feathers of the other groups of birds including the water birds, omnivores, insectivore-frugivores, insectivores, and granivores. These metals might have a preference for the pigments that give birds their coloring, for example, the darker black and iridescent blue feathers contained considerable amounts of Fe and Cu, while Zn was noticed in the iridescent feathers [48,49]. The feather Cd levels of the six groups of birds in the present study were below the threshold level (2 ppm), but the Pb concentrations were critically above the threshold (4 ppm) that affects reproductive success in birds [7,43].…”
Section: Discussioncontrasting
confidence: 47%
“…Bird feathers are the sites of heavy metal accumulation and excretion and are considered significant bioindicators for long-term exposure to environmental pollution [8,9]. Earlier research has reported that Zn and Cu are essential metals accumulated in feathers of most predatory birds, including the Common Buzzard, Barn Owl, Eurasian Sparrowhawk, Osprey, and Common Kestrel [47,48]. Similar to our results, in addition to predatory birds, the highest proportions of Zn and Cu were detected in the feathers of the other groups of birds including the water birds, omnivores, insectivore-frugivores, insectivores, and granivores.…”
Section: Discussionmentioning
confidence: 99%
“…Total 200 μM of purified proteins of SufT WT, SufT C62A, BSA (negative control) and catalase (positive control) were saturated with 300 μM of FeSO 4 followed by desalting by PD10 column. Protein samples were estimate as described earlier [ 72 ] with little modifications. Briefly, equal volume of protein samples (100 μL) was cold digested with 10 mL of nitric acid overnight.…”
Section: Methodsmentioning
confidence: 99%